circ-NOL10 regulated by MTDH/CASC3 inhibits breast cancer progression and metastasis via multiple miRNAs and PDCD4 - Yujie Cai; Xing Zhao; Danze Chen; Fan Zhang; Qiuyang Chen; Chang-Chun Shao; Yan-Xiu Ouyang; Jun Feng; Lili Cui; Min Chen; Jianzhen Xu (Elsevier, 2021)
Circular RNAs (circRNAs) play important roles in carcinogenesis. Here, we investigated the mechanisms and clinical significance of circ-NOL10, a highly repressed circRNA in breast cancer. Subsequently, we also identified RNA-binding proteins (RBPs) that regulate circ-NOL10. Bioinformatics analysis was utilized to predict regulatory RBPs as well as circ-NOL10 downstream microRNAs (miRNAs) and mRNA targets. RNA immunoprecipitation, luciferase assay, fluorescence in situ hybridization, cell proliferation, wound healing, Matrigel invasion, cell apoptosis assays, and a xenograft model were used to investigate the function and mechanisms of circ-NOL10 in vitro and in vivo. The clinical value of circ-NOL10 was evaluated in a large cohort of breast cancer by quantitative real-time PCR. Circ-NOL10 is downregulated in breast cancer and associated with aggressive characteristics and shorter survival time. Upregulation of circ-NOL10 promotes apoptosis, decreases proliferation, and inhibits invasion and migration. Furthermore, circ-NOL10 binds multiple miRNAs to alleviate carcinogenesis by regulating PDCD4. CASC3 and metadherin (MTDH) can bind directly to circ-NOL10 with characterized motifs. Accordingly, ectopic expression or depletion of CASC3 or MTDH leads to circ-NOL10 expression changes, suggesting that these two RBPs modulate circ-NOL10 in cancer cells. circ-NOL10 is a novel biomarker for diagnosis and prognosis in breast cancer. These results highlight the importance of therapeutic targeting of the RBP-noncoding RNA (ncRNA) regulation network.